Mammomonogamus laryngeus: A HUMAN CASE REPORT IN FLORIANOPOLIS, SANTA CATARINA, BRAZIL - Alves de Almeida, Patricia; Amélia Martins, Fernanda; Paula Lazzaretti Marostega, Ana; Jose de Carvalho Pinto, Carlos; Ana Bricarello, Patrizia; Mattos Lima, Lenilza (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Mammomonogamus laryngeus (sin.: Syngamus laryngeus) is a nematode which parasites the respiratory tract of some animals. It is occasionally seen in humans, who present symptoms similar to other diseases with respiratory manifestations, such as a chronic dry cough and chest pain, in addition to a “foreign body” sensation in the throat. It can be diagnosed through rhinolaryngoscopy or bronchoscopy examinations, but this often occurs only after spontaneous expectoration of the worms, a long period of symptomatology and the use of several types of medication. In this report, we describe a case of syngamosis in Florianópolis (Santa Catarina, Brazil). The patient consulted several health professionals during the course of the disease and was prescribed numerous drugs. Diagnosis was eventually reached after the spontaneous expectoration of a nematode couple.